Vitamin D Status is Independently Associated with Insulin Resistance in Patients with Type 2 Diabetes Mellitus - Zhao H; Tang Y; Zheng C; Ren L; Song G (Dove Medical Press, 2021)
Hang Zhao,1 Yong Tang,1 Chong Zheng,2 Luping Ren,1,* Guangyao Song1,* 1Endocrinology Department, Hebei General Hospital, Shijiazhuang, Hebei, 050051, People’s Republic of China; 2Pediatric Orthopaedics, Shijiazhuang the Third Hospital, Shijiazhuang, Hebei, 050011, People’s Republic of China*These authors contributed equally to this workCorrespondence: Luping Ren; Guangyao Song 348, Heping West Road, Shijiazhuang, Hebei, 050051, People’s Republic of ChinaTel +8631185988975; +8631185988556Email renluping1122@163.com; sguangyao2@163.comPurpose: This study aimed to examine whether 25-hydroxyvitamin D (25OHD) levels (an indicator of vitamin D status) are independently associated with insulin resistance (IR) in patients with type 2 diabetes mellitus (T2DM).Patients and Methods: This was a cross-sectional study. Participants with T2DM were recruited from the Department of Endocrinology in Hebei General Hospital according to inclusion and exclusion criteria. Data on basic characteristics and blood parameters were collected. We used the IR index (20/[fasting C-peptide × fasting plasma glucose]) to evaluate IR. Potential confounding factors were selected from comparisons among different IR index groups of quartiles and were adjusted in different models.Results: We included 172 subjects (121 men and 51 women) whose mean age was 53.2± 10.6 years. Body mass index (BMI), DM course, insulin use, glycated hemoglobin (HbA1c), fasting blood glucose, fasting C-peptide, triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), apolipoprotein A1 (ApoA1), and albumin were differed among different IR-index groups (all P value < 0.05). In models 1 and 2, no or some confounding factors were adjusted for, and we found that there was no relationship between 25OHD and the IR index. In model 3, when all confounding factors (DM course, insulin use, BMI, HbA1c, TG, HDL-C, ApoA1, albumin and other bone turnover markers) were adjusted for, the IR index was increased by 5.6% when 25OHD levels increased by 1 ng/mL (odds ratio: 1.056; 95% confidence interval: 1.009, 1.105).Conclusion: Vitamin D is independently associated with IR in patients with T2DM.Keywords: diabetes mellitus, type 2, vitamin D, insulin resistance